2018
DOI: 10.30941/cestems.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of novel axial flux magnetically geared and conventional axial flux permanent magnet machines

Abstract: In this paper, a performance comparison between the novel axial flux magnetically geared machines (AFMG) and the conventional axial flux YASA machine is presented. The AFMG and YASA machines have the same stator construction in which segments are equipped with concentrated windings to form the stator. However, the AFMG machine has two rotors with different pole-pair numbers. Magnetic gear effect can be obtained to increase the torque density. The performance comparisons at no-load and on-load conditions are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Actually, the surface-type FMPM machines can also be designed with axial flux, which are even more promising in achieving compact structures and high torque densities. Figure 9 shows the configuration of an axial-flux MGPM machine for power split application in hybrid electric vehicles [24], and comparative investigation showed that it can achieve significantly higher torque than the conventional axial-flux YASA machine [25]. The application of an axial-flux MGPM machine in a wind turbine was investigated in [26], and a prototype with a torque density of 7.8 kNm/m 3 was designed, fabricated, and tested.…”
Section: Surface-type Fmpm Machinesmentioning
confidence: 99%
“…Actually, the surface-type FMPM machines can also be designed with axial flux, which are even more promising in achieving compact structures and high torque densities. Figure 9 shows the configuration of an axial-flux MGPM machine for power split application in hybrid electric vehicles [24], and comparative investigation showed that it can achieve significantly higher torque than the conventional axial-flux YASA machine [25]. The application of an axial-flux MGPM machine in a wind turbine was investigated in [26], and a prototype with a torque density of 7.8 kNm/m 3 was designed, fabricated, and tested.…”
Section: Surface-type Fmpm Machinesmentioning
confidence: 99%
“…Substituting (2)-(4) into (1) gives (5). The active power is defined by (6) and finally the outer diameter is calculated from 7:…”
Section: Analytical Designmentioning
confidence: 99%
“…In double‐rotor AFPM machines in which PMs of opposite polarity face each other, magnetic flux from one rotor flows into the other without travelling circumferentially through the stator core; this may be eliminated which can lead to the removal of associated loss and cogging torque, although at the cost of a higher electromagnetic air gap. Previously published papers have mostly focused on conventional AFPM machines with a ferromagnetic core [4, 5]. Coreless AFPM machines have been studied less frequently.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many applications, mechanical gears are necessary to improve the torque, while they increase the manufacture and maintenance cost, as well as the system volume [4][5][6]. In order to avoid the mechanical gears, the axial flux permanent magnet (AFPM) machine has recently attracted much attention from scholars [7][8][9]. The high aspect ratio gives them many advantages such as compactness, high torque density, and good heat dissipation [10,11], which makes AFPM machines very suitable for direct-drive systems [12].…”
Section: Introductionmentioning
confidence: 99%